Explorando mundos con mis pequeños gigantes - Hernández Giraldo, Yfalia Andrea (Educación, Ciencias Humanas y Sociales, 2018)
This work is done with children in their early childhood, in the ages between 4 and 5. The study was performed in the Children´s home called “Semillitas” located in Marinilla, Antioquia. In this place it was decided to work with tale stories, songs and videos in order to discover the children´s feelings. We found that there is not better way than to let the children express themselves through what they like and at the same they can create narrations which will always reflect what they are learning, what they desire or they simply let their imagination fly. It is on this that learning how to read in a conventional way consists of, making the children feel less pressure and letting them enjoy what their previous knowledge can offer them specially the album books. To sum up, it is important that the children can make a successful transit in the language area, coming, in this way, near to books, songs or videos. All this with the idea that we, as teachers can help the children to enrich their vocabulary, but most important of all is that the children can have fun and strengthen their imagination.